2007
DOI: 10.1590/s0103-84782007000100018
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação de gesso agrícola e especiação iônica da solução de um Latossolo sob sistema plantio direto

Abstract: Gypsum application and ionic speciation of the solution from an Oxisol under no-till system RESUMO O baixo teor de Ca e a toxicidade por Al são importantes limitações à produtividade das culturas em solos ácidos brasileiros. É possível aumentar o teor de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
29

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 9 publications
6
28
0
29
Order By: Relevance
“…The pH increased after black oat and maize cultivation in the solution of all treatments; this may indicate OH -/HCO 3 -exudation by plant roots, as a form of maintaining the electrochemical equilibrium, due to the absorption of anions such as NO 3 -, whose concentration in the solution decreased in all layers due to the cultivation of two grass species, which have a high demand for N, but also for P and SO 4 2-in the surface layers (Table 1) (Gahoonia et al, 1992). Zambrosi et al (2007) observed percentages higher than 40 % of AlHPO 4 + in the solution in a clayey soil treated with gypsum, with a pH value in solution close to 5.0, which was similar to that observed in the deeper soil layers in all treatments in the 1 st sampling, indicating that aside from the pH, the soil properties have a great influence on P species distribution in the soil solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH increased after black oat and maize cultivation in the solution of all treatments; this may indicate OH -/HCO 3 -exudation by plant roots, as a form of maintaining the electrochemical equilibrium, due to the absorption of anions such as NO 3 -, whose concentration in the solution decreased in all layers due to the cultivation of two grass species, which have a high demand for N, but also for P and SO 4 2-in the surface layers (Table 1) (Gahoonia et al, 1992). Zambrosi et al (2007) observed percentages higher than 40 % of AlHPO 4 + in the solution in a clayey soil treated with gypsum, with a pH value in solution close to 5.0, which was similar to that observed in the deeper soil layers in all treatments in the 1 st sampling, indicating that aside from the pH, the soil properties have a great influence on P species distribution in the soil solution.…”
Section: Discussionmentioning
confidence: 99%
“…Continued applications of PS, a multielement fertilizer, are expected to induce changes in the chemical composition and distribution of P species in the soil solution, together with crop cultivation, which can alter the concentration of elements in the soil solution by absorption and accumulation in plant tissues, by exudation of organic compounds and by changes in pH through the release of OH -or H + (Gahoonia et al, 1992). The P species in soil solution can be estimated with specific software such as Visual Minteq, since P bioavailability and mobility depend on the concentration and chemical species in the solution (Nolla and Anghinoni, 2006;Zambrosi et al, 2007;Girotto et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…O experimento com milho avaliou seis doses de gesso agrícola (0 t ha -1 , 0,5 t ha -1 , 1 t ha -1 , 2 t ha -1 , 4 t ha -1 e 8 t ha -1 ) (16 % de enxofre e 24 % de cálcio), com aplicação de 2 t ha (Zambrosi et al 2007, Maschietto 2009). O aumento dos teores de Mg trocável em profundidade, em relação ao Ca trocável, pode estar relacionado ao fato de o Mg ser menos fortemente retido no complexo de troca, devido ao seu maior raio hidratado e menor eletronegatividade, possibilitando maior movimentação no perfil.…”
Section: Methodsunclassified
“…The effects of PG on Al 3+ have been associated with the formation of Al hydroxylated structures in the soil, as a result of ligand exchange between OH − from the surfaces of hydrated Fe or Al oxides and SO 4 2− provided by PG (Reeve and Sumner, 1972), as well as the formation of an ionic pair between Al 3+ and SO 4 2− or fluoride (F − ) (Zambrosi et al, 2007). Phosphogypsum contains approximately 15 % S and 0.6-3.2 % F, and even when considering the role of SO 4 2− in Al 3+ complexation, F − may be even more effective in this reaction (Carvalho and Raij, 1997;Zambrosi et al, 2007), which may explain why PG is more efficient than natural gypsum (gypsite) in complexing Al 3+ . In clayey Oxisols, Rampim et al (2011) and Caires et al (1999) (2) Linear adjust and R 2 value after the bar; * and **: significant at p<0.05 and p<0.01, respectively; ns: not significant.…”
Section: Chemical Properties Of Soil Fertilitymentioning
confidence: 99%
“…Concomitantly, Mg 2+ and K + -the latter only rarely -are displaced from the soil exchange sites in top layers and then move along with water to the subsurface (Caires et al, 2011b to plant roots can occur (Toma et al, 1999), due to the formation of ionic pairs between Al 3+ and the sulfate (SO 4 2− ) or fluoride (F − ) contained in PG (Zambrosi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%